1972
DOI: 10.1111/j.1399-6576.1972.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency Positive Pressure Ventilation During Anaesthesia and Routine Surgery in Man

Abstract: The respiratory and circulatory conditions in high frequency positive pressure ventilation (HFPPV) in the dog have been investigated previously. By means of expiratory resistance a positive intratracheal pressure was maintained throughout the respiratory cycle. Adequate ventilation was achieved at low intratracheal and transpulmonary pressures.A clinical test of this form of ventilation was conducted in connection with routine surgery in 15 patients; in 11 patients neuroleptic analgesia and in four patients th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In 197 1, this HFPPV technique was therefore investigated in 15 patients scheduled for routine surgery under general anesthesia (2). Adequate oxygenation and ventilation were achieved with HFPPV at rates of 60-1 10 bpm and insumation times of 15-30y0.…”
Section: First Clinical Studies O F Hfppvmentioning
confidence: 99%
“…In 197 1, this HFPPV technique was therefore investigated in 15 patients scheduled for routine surgery under general anesthesia (2). Adequate oxygenation and ventilation were achieved with HFPPV at rates of 60-1 10 bpm and insumation times of 15-30y0.…”
Section: First Clinical Studies O F Hfppvmentioning
confidence: 99%
“…Subsequent studies showed that the technique could also be used in anaesthetised patients. 3 Further developments led to the use of this technique for bronchoscopy, laryngoscopy, paediatric anaesthesia, and neonatal respiratory care.45 A trial in 12 patients with adult respiratory distress syndrome, however, showed no convincing benefit over conventional mechanical ventilation. 6 There have been few detailed studies of gas exchange during HFPPV, since many of the systems do not permit complete separation of inspired and expired gas.…”
Section: High Frequency Positive Pressure Ventilationmentioning
confidence: 99%
“…33 These studies showed that after a deep breath arterial Po2 was better maintained and the mortality rate less in the group of rabbits treated with HFO, while histological examination showed minimal lung damage in the HFO group, but appreciable hyaline membrane formation in the group submitted to conventional mechanical ventilation. It was suggested that the rabbits in the HFO group were maintained on the descending limb of the P-V curve, so that lung volumes were higher for a given transpulmonary pressure, and that the small tidal volumes resulted in fewer intraregional stresses than in the conventional mechanical ventilation group (3) convective transport of gases resulting from the asymmetry between the inspiratory and the expiratory flow profiles; (4) longitudinal dispersion from interaction between the axial stream and radial dispersion due to turbulence; (5) molecular diffusion in the alveolar capillary membrane region.…”
Section: High Frequency Positive Pressure Ventilationmentioning
confidence: 99%
See 2 more Smart Citations